2016
DOI: 10.1111/apt.13740
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: a Lactobacillus GG and micronutrient‐containing mixture is effective in reducing nosocomial infections in children, vs. placebo

Abstract: A mixture containing Lactobacillus GG and micronutrients may reduce the incidence of nosocomial infections, supporting the hypothesis that this may represent a valid strategy to prevent nosocomial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
(63 reference statements)
0
20
0
3
Order By: Relevance
“…Prevention of HAI is one of the top priorities of the Center of Diseases Control and Prevention (CDC), but preventive concepts so far did not addressed the potential contribution of the gut microbiota of hospitalized patients to HAI. Interestingly, a recent study showed that in a randomized, double-blind, placebo-controlled trial in hospitalized children, an intake of a mixture containing Lactobacillus GG and micronutrients reduced the incidence of HAI, supporting the hypothesis that certain manipulations of the intestinal microbiota may provide a safeguarding strategy to prevent such infections 15 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Prevention of HAI is one of the top priorities of the Center of Diseases Control and Prevention (CDC), but preventive concepts so far did not addressed the potential contribution of the gut microbiota of hospitalized patients to HAI. Interestingly, a recent study showed that in a randomized, double-blind, placebo-controlled trial in hospitalized children, an intake of a mixture containing Lactobacillus GG and micronutrients reduced the incidence of HAI, supporting the hypothesis that certain manipulations of the intestinal microbiota may provide a safeguarding strategy to prevent such infections 15 .…”
Section: Discussionmentioning
confidence: 95%
“…As hospitalized patients are at increased risk for acquiring HAIs, identifying the dysbiosis associated with this population can serve as a first step toward specific therapeutic interventions in this population. In support of this concept is a recent study that showed that a mixture containing Lactobacillus GG and micronutrients reduced the incidence of HAI 15 .…”
Section: Introductionmentioning
confidence: 90%
“…Another study with L. rhamnosus GG was performed in 90 hospitalized children, and they received L. rhamnosus GG plus vitamin B, vitamin C, and zinc or placebo. The consumption of a combination of L. rhamnosus GG and micronutrients was effective in reducing the incidence of gastrointestinal infections and the length of hospitalization compared to placebo [ 43 ]. Furthermore, the duration and severity of symptoms were reduced [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Einen völlig anderen Stellenwert hat das lokal wirksame Antibiotikum Rifaximin. Es wirkt vor allem auf die darmständige Mikrobiota und wird nur zu 1 % systemisch resorbiert [106] [112,113]. Jedoch liegen dazu bislang widersprüchliche Ergebnisse vor.…”
Section: Antibiotikaunclassified